2021
DOI: 10.33425/2771-666x.1006
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan-Graft-Sodium Alginate Encapsulated Vanadium Pentoxide (V2 O5 ) Nanocomposite for Adsorption and Antimicrobial Studies

Abstract: A hybrid vanadium pentoxide (V2 O5 )/chitosan-graft-sodium alginate nanocomposite was synthesized via the graft co-polymerization technique. The nanocomposite was characterized by X-ray diffraction analysis, Fourier transform infra-red spectroscopy, scanning electron microscopy and transmission electron spectroscopy. Batch studies was employed for the adsorption of model methyl violet onto V2 O5 /chitosan-graft-sodium alginate from aqueous solution. The adsorption best suited the Langmuir isotherm and pseudo-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The adsorption data obtained from 50 mg of SBVO8 compound in 5 ppm-40 ppm(5 ppm step size) of MB dye solution was fitted to the Freundlich, Langmuir and Dubinin-Radushkevich (DÀ R)and Temkin adsorption isotherm models. [11] Langmuir isotherm model showcases a uniform surface adsorption. The linear form is…”
Section: Adsorption Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…The adsorption data obtained from 50 mg of SBVO8 compound in 5 ppm-40 ppm(5 ppm step size) of MB dye solution was fitted to the Freundlich, Langmuir and Dubinin-Radushkevich (DÀ R)and Temkin adsorption isotherm models. [11] Langmuir isotherm model showcases a uniform surface adsorption. The linear form is…”
Section: Adsorption Experimentsmentioning
confidence: 99%
“…[11] et al also reported V 2 O 5 /chitosan graft sodium alginate nanocomposite for the adsorption of model dye, methyl violet, from water and the effects of adsorption parameters were investigated and analyzed by different adsorption isotherms. [11] V 2 O 5 compounds intercalated with alkylimidazolium, the cation of an ionic liquid, exhibit lower adsorption capacities for dyes such as methyl orange and rhodamine B. However, their adsorption efficiency for methylene blue is higher, reaching 81 wt % within a short time frame, and they completely removed 10 ppm of methylene blue within 80 minutes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using nano-metal oxides as adsorbent materials is an efficient technique for water cleaning from major pollutants like aromatic compounds, heavy metals, and dyes. In recent years, finding clean water for human consumption and other applications has become more challenging because of the increased demand for water resources and pollution by anthropogenic and natural means [16]. Industries such as dyeing, textile, paint, and leather tanning are the largest sources of the release of wastewater [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Industries such as dyeing, textile, paint, and leather tanning are the largest sources of the release of wastewater [17,18]. It is assumed that the wastewater generated after the dyeing and finishing processes from textile plants is regarded as the most contaminant of all the industrial sources, considering the magnitude and composition of the released effluents [16].…”
Section: Introductionmentioning
confidence: 99%